Association of Parkinson’s Disease With Microbes and Microbiological Therapy - Chen, Zhao-Ji; Liang, Cheng-Yu; Yang, Li-Qing; Ren, Si-Min; Xia, Yan-Min; Cui, Lei; Li, Xiao-Fang; Gao, Bu-Lang (Frontiers in Cellular and Infection Microbiology, 2021)
Parkinson’s disease (PD) is the most common movement disorder in the world and， affectsing 1-2 per 1000 of the population. The main pathological changes of PD are damage of dopaminergic neurons in substantia nigra of the central nervous system and formation of Lewy bodyies. These pathological changes also occur in the intestinal tract and are strongly associated with changes in intestinal flora. By reviewing the research progress in PD and its association with intestinal flora in recent years, this review expounded the mechanism of action between intestinal flora and PD as well as the transmission mode of α - synuclein in neurons. In clinical studies, β diversity of intestinal flora in PD patients was found to change significantly, with Lactobacillusaceae and verrucomicrobiaceae Verrucomicrobiaceae being significantly increased and lachnospiraceae Lachnospiraceae and prevotellaceae Prevotellaceae being significantly decreased. In addition, a longer PD course was associated with fewer bacteria and probiotics producing short chain fatty acids, but more pathogenic bacteria. Moreover, the motor symptoms of PD patients may be related to Enterobacteriaceae and bacteria. Most importantly, catechol-O-methyltransferase inhibitors and anticholinergic drugs could change the intestinal flora of PD patients and increase the harmful flora, whereas other anti-PD drugs such as levodopa, dopamine agonist, monoamine oxidase inhibitors, and amantadine did not have these effects. Probiotics, prebiotics, and synbiotics treatment had some potential values in improving the constipation of PD patients, promoting the growth of probiotics, and improving the level of intestinal inflammation. At present, there were only a few case studies and small sample studies which had have found certain clinical efficacy of fecal microbiome transplantstransplantation. Further studies are necessary to elaborate the relationship of PD with microbes..